Overexpression of Circular RNA circ_0013587 Reverses Erlotinib Resistance in Pancreatic Cancer Cells Through Regulating the miR-1227/E-Cadherin Pathway - Xu, Huiting; Chen, Runzhi; Shen, Qian; Yang, Dongmei; Peng, Hui; Tong, Jin; Fu, Qiang (Frontiers in Oncology, 2021)
Background Erlotinib, a small-molecule epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, demonstrated therapeutic efficacy against pancreatic cancer. However, acquired resistance to erlotinib in pancreatic cancer is widely observed, and the exact mechanisms have not been fully explored until now. We examined the role of circular RNA circ_0013587 in the acquired resistance to erlotinib in pancreatic cancer cells and explored the underlying mechanisms. Methods We selected erlotinib-resistant pancreatic cancer cells from the AsPC-1 cell line. The expression of circ_0013587 was examined by qRT-PCR assays. The effects of circ_0013587 on pancreatic cancer cell proliferation, invasion, and erlotinib resistance were assessed by cell functional assays. Bioinformatic analysis and dual-luciferase reporter assays identified circ_0013587 and E-cadherin as direct targets of miR-1227. Mouse xenograft models were employed to investigate the function of circ_0013587 in erlotinib resistance of tumors in vivo. Results Circ_0013587 expression was significantly reduced in erlotinib-resistant AsPC-1 cells. We found that increasing circ_0013587 levels in erlotinib-resistant AsPC-1 cells re-sensitized them, whereas reducing circ_0013587 levels in erlotinib-sensitive AsPC-1 cells made them resistant. Mechanically, circ_0013587 released E-cadherin from the suppression of miR-1227, leading to E-cadherin up-regulation. Rescue assays highlighted that circ_0013587 reversed erlotinib resistance in pancreatic cancer cells by increasing E-cadherin levels through reducing the expression of miR-1227. Furthermore, circ_0013587 overexpression sensitized erlotinib-resistant AsPC-1 cells to erlotinib in xenograft models. Conclusions Our results demonstrated that down-regulation of circ_0013587 contributes to acquired resistance to erlotinib in pancreatic cancer cells through mediating the miR-1227/E-cadherin pathway and that circ_0013587 is a potential target molecular to overcome erlotinib resistance.